Real-World Efficacy of Daclatasvir and Sofosbuvir, With and Without Ribavirin, in HIV/HCV Coinfected Patients With Advanced Liver Disease in a French Early Access Cohort. (1st May 2017) - Lacombe, Karine; Fontaine, Hélène; Dhiver, Catherine; Metivier, Sophie; Rosenthal, Eric; Antonini, Teresa; Valantin, Marc Antoine; Miailhes, Patrick; Harent, Stanislas; Batisse, Dominique; Pageaux, Georges-Philippe; Chas, Julie; et al.
Abstract : Background: Efficacious, well-tolerated, direct antiviral agents have drastically changed the prognosis of hepatitis C virus (HCV) disease, but real-world data for oral treatments are limited in key populations such as HIV/HCV coinfection with advanced liver disease. Daclatasvir (DCV) efficacy and safety was assessed in the French "Autorisation Temporaire d'Utilisation" (ATU) program, providing DCV ahead of market authorization to patients with advanced HCV disease without other treatment options. Methods: This was a subanalysis of HIV/HCV coinfected ATU patients treated with DCV plus sofosbuvir (SOF). Recommended duration was 24 weeks; addition of ribavirin (RBV) and/or shorter treatment was at the physician's discretion. The primary efficacy analysis was sustained virologic response at posttreatment week 12 (SVR12; modified intention-to-treat). Safety was assessed by spontaneous adverse event reporting. Results: The efficacy population (N = 407) was mostly cirrhotic (72%, of whom 18% were decompensated), HCV treatment–experienced (82%), and infected with genotypes 1 (69%), 3 (12%), or 4 (19%). Median CD4 was 555 cells/mm 3 ; 95% had HIV RNA <50 copies/mL. Most (74%) were treated for 24 weeks; 14% received RBV. SVR12 was 92% overall (95% confidence interval: 88.6% to 94.0%); 90% (86.4% to 93.2%) in patients with cirrhosis; 95% (88.9% to 97.5%) in patients without cirrhosis. SVR12 was consistent across HCV genotypes and antiretroviral regimens. Among 617 patients with safety data, 7 discontinued for an adverse event and 10 died. Conclusions: DCV+SOF±RBV achieved high SVR12 and was well tolerated in this large real-world cohort of HIV/HCV coinfected patients with advanced liver disease. Abstract : Supplemental Digital Content is Available in the Text.